Loss of genomic diversity in a neisseria meningitidis clone through a colonization bottleneck - Lamelas, Araceli; Junghanss, Thomas (Genome biology and evolution, 2018)
Abstract. Neisseria meningitidis is the leading cause of epidemic meningitis in the “meningitis belt” of Africa, where clonal waves of colonization and disease